(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Post modernism is a word used to characterize varieties in ways individuals think; especially the way they see truth and reality. Postmodern in Indian English literature finds fragmentariness in portrayal and character structure uniquely in contrast to its British or American supplement. In post modernism, there is a fixation on tensions in the truth of humanity. The photo of life depicted by them suits irrelevance, purposelessness and negligibility of human survival through the employment of gadgets such as Inconsistency, Permutation, Incoherence, Uncertainty, Excess, Short Circuit et cetera. Post-modernist literature shows turbulent state of the world. Amitav Ghosh is one among the post modernists. Amitav Ghosh is one the most striking writers of the postmodernism time. He exceeded expectations in this time with his pattern of enchantment authenticity. The Shadow Lines is a story told by an anonymous narrator in memory. It’s a non-direct story told as though assembling the bits of a jigsaw puzzle in the memory of the narrator. This style of composing is both one of a kind and charming; unfurling thoughts together as time and space mix and helping the narrator comprehend his past better. Spinning around the subject of nationalism in an inexorably globalized world, Ghosh questions the genuine importance of political opportunity and the fringes which basically appear to both build up and partitioned. The novel navigates through very nearly seventy years through the recollections of individuals, which the narrator remembers and describes, giving their perspective along with his own. Despite the fact that the novel is based to a great extent in Kolkata, Dhaka, and London, it appears to reverberate the conclusions of entire Southeast Asia, with clear suggestions of Independence and the strings of Partition. Amitav Ghosh, one of the postmodernist novelists in English is colossally affected by the political and socialized region of post autonomy period. Being a social anthropologist and enterprising voyager, he depicts the present situation that have inundated the world. To postmodernists like Ghosh, national boundaries, traditions and customs are an impediment to human communication. Nationalism brings forth wars. Along these lines, they talk for globalization. Ghosh, being a wandering cosmopolitan, his novels minutely and legitimately depict multinational concerns. In The Shadow Lines and The Glass Palace, Amitav Ghosh makes his characters to take their own particular stand and avow their perspectives which result in some cases into agreeable connections while numerous different circumstances into discordant ones. This very conflict among them makes these novels truly postmodern which stands more for the globalization than for nationalization.